Estabilidade, polimorfismo, dissolução e correlação in vivo-in vitro de Darunavir comprimidos - Corrêa, Josilene Chaves Ruela [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Darunavir, a protease inhibitor, constitute the highly active antiretroviral therapy against the acquired immunodeficiency syndrome. It is one of agents given free by the Brazilian Health System (SUS). Generic products have contributed to the maintenance and the policy of free distribution of medicines by the decreasing of costs of these products. In this way, this study seeks to provide information on the physical and chemical behavior and stability of the drug and formulation, facing different weather conditions, as well as provide information on their solubility and release from the formulation. It also aims to provide in vitro and in silico tools to contribute in the near future, for the production of new products containing darunavir, especially generic medicines. Therefore, the solubility of the drug was investigated in different media. The low aqueous solubility of the drug was observed, and suitable media for dissolution testing were chosen. The in vitro dissolution profile of darunavir and the in vivo absorption from Prezista® (tablets containing 300 mg of drug) were investigated. It was obtained a discriminating dissolution profile of the product and a method of quantification by spectrophotometry derivative was developed and validated. A correlation between the data of in vitro dissolved fraction and in vivo absorbed fraction of darunavir was achieved (r2 = 0.95). This is a predictive method to evaluate the in vivo performance of darunavir from immediate-release tablets, based on in vitro data, and it is important to minimize the use of animals and humans in experiments during the development of new medicines containing darunavir. In addition, an in silico tool was developed and validated for predicting the oral bioavailability of darunavir formulations, from their dissolution profile. For this, physiologically based pharmacokinetic modeling was applied through Simcyp® software. These, in vitro and in silico tools, assist in ...

O darunavir, antirretroviral inibidor de protease, compõe a terapia considerada altamente eficaz no tratamento da síndrome da imunodeficiência humana adquirida, e é um dos fármacos disponibilizados gratuitamente pelo Sistema Único de Saúde (SUS). Os produtos genéricos têm contribuído para a manutenção e abrangência desta política de distribuição gratuita de medicamentos, ao reduzir os custos desses produtos. Neste propósito, este estudo busca fornecer informações sobre o comportamento físicoquímico e estabilidade do fármaco e da formulação, diante de diferentes condições climáticas, bem como, sobre sua solubilidade e liberação a partir da formulação. Além disso, pretende apresentar ferramentas in vitro e in silico que contribuam, no futuro próximo, para a produção de novos produtos contendo darunavir que apresentem alta qualidade, especialmente, genéricos do medicamento referência. Para tanto, a solubilidade do fármaco foi investigada em diferentes meios. A baixa solubilidade aquosa do fármaco foi verificada, e os meios adequados aos testes de dissolução foram escolhidos. O perfil de dissolução in vitro do darunavir e de absorção in vivo a partir papel dos comprimidos de Prezista® contendo 300 mg de fármaco foram investigados. Obtevese um perfil de dissolução discriminativo para o produto e um método de quantificação por espectrofotometria derivada foi desenvolvido e validade. Uma correlação entre os dados de fração dissolvida in vitro e fração absorvida in vivo do darunavir foi alcançada (r2= 0,95). Este é um método preditivo para avaliar o desempenho in vivo do darunavir a partir de comprimidos de liberação imediata, com base em dados in vitro, e é importante para minimizar o uso de animais e seres humanos em experimentos durante o desenvolvimento novos produtos farmacêuticos contendo darunavir. Além disso, uma ferramenta in silico foi desenvolvida e validada para a previsão da ...
Keywords: Polimorfismo (Cristalografia); Soropositividade para HIV; AIDS (Doença); Fármacos; Medicamentos - Desenvolvimento; Drug development